Can host reaction animal models be used to predict and modulate skin regeneration?. (2nd February 2016) - Santos, T. C.; Reis, R. L.; Marques, A. P.
Abstract: The study of host reactions in the biomedical and tissue engineering (TE) fields is a key issue but somehow set aside where TE constructs are concerned. Every day new biomaterials and TE constructs are being developed and presented to the scientific community. The combination of cells and biomolecules with scaffolding materials, as TE constructs, make the isolation and the understanding of the effect of each one those elements over the overall host reaction difficult. Eventually, all variables influence the host reaction and the performance of the constructs. For this reason, current assessment of the in vivo performance of TE constructs follows individual approaches, using specific animal models to independently provide insights regarding the contribution of the biomaterials/scaffolds towards the host reaction, and of all the constructs regarding their functionality. Skin wound healing progress into tissue regeneration or repair is highly dependent on the specificities of the inflammatory stage, as demonstrated by comparison between fetal and adult mechanisms. Thus, it would be expected that insights acquired from host tissue reaction evaluation to biomaterials/scaffolds would be explored to predict healing progression and improve the functionality of skin TE constructs. The rational of this review is to make a comprehensive analysis of to what extent the knowledge obtained from the evaluation of in vivo host reactions to implantable biomaterials/scaffolds has been used in the design of skin TE strategies, by promoting tissue regeneration rather than repair. Copyright © 2016 John Wiley & Sons, Ltd.